2021
DOI: 10.1523/jneurosci.0647-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

A Precuneal Causal Loop Mediates External and Internal Information Integration in the Human Brain

Abstract: Human brains interpret external stimuli based on internal representations. One untested hypothesis is that the default-mode network (DMN), widely considered responsible for internally oriented cognition, can decode external information. Here, we posit that the unique structural and functional fingerprint of the precuneus (PCu) supports a prominent role for the posterior part of the DMN in this process. By analyzing the imaging data of 100 participants performing two attention-demanding tasks, we found that the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 81 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…It has been identified that the default mode network (DMN) exhibits internal activities, also referred to as the "task-negative network" (Andrews-Hanna, 2012;Andrews-Hanna et al, 2014), whereas the lateral frontoparietal areas related to the network of dorsal attention (DAN; Mallas et al, 2021) and executive control (ECN; Martin-Signes et al, 2019) mediate taskdriven stimuli (Xin et al, 2021;i.e., task-positive network). These two sets of regions are reported to be negatively correlated with healthy adults, anesthetic patients, or patients with prolonged DoC (He et al, 2014;Palanca et al, 2015), both under resting-state or attention-demanding processes (Lyu et al, 2021). In another case, according to the regulating function, the brain networks could be classified into higher order networks [the DMN, ECN, DAN, and salience network (SN)] and sensory-related (perceptual processing) lower order networks including the sensory input auditory network (AN; Braga et al, 2017), visual network (VN;, and sensorimotor network (SMN; Liang et al, 2015; Figure 1).…”
Section: Functional Network In Prolonged Docmentioning
confidence: 99%
“…It has been identified that the default mode network (DMN) exhibits internal activities, also referred to as the "task-negative network" (Andrews-Hanna, 2012;Andrews-Hanna et al, 2014), whereas the lateral frontoparietal areas related to the network of dorsal attention (DAN; Mallas et al, 2021) and executive control (ECN; Martin-Signes et al, 2019) mediate taskdriven stimuli (Xin et al, 2021;i.e., task-positive network). These two sets of regions are reported to be negatively correlated with healthy adults, anesthetic patients, or patients with prolonged DoC (He et al, 2014;Palanca et al, 2015), both under resting-state or attention-demanding processes (Lyu et al, 2021). In another case, according to the regulating function, the brain networks could be classified into higher order networks [the DMN, ECN, DAN, and salience network (SN)] and sensory-related (perceptual processing) lower order networks including the sensory input auditory network (AN; Braga et al, 2017), visual network (VN;, and sensorimotor network (SMN; Liang et al, 2015; Figure 1).…”
Section: Functional Network In Prolonged Docmentioning
confidence: 99%
“…For example, recent literature using graph theoretic metrics and information theory has provided a new perspective for how we understand consciousness; it suggests that the posteromedial cortex (PMC; PCC/PCU), standing out as a hub for the whole-brain information exchange, affords the complexity that consciousness emerges from [66][67][68] . There have also been theoretical arguments hinting at the PCU's role in information integration between the internal and external worlds 69,70 , a fundamental component of conscious processing 71,72 .…”
Section: Discussionmentioning
confidence: 99%
“…While the meta-analysis by Uncapher and Wagner was focused on lateral parietal structures, a similar pattern of functional heterogeneity has also been proposed for midline parietal subregions of the DMN (Kernbach et al, 2018). Particularly the dorsal Prc is involved in switching between DMN activity and activity of task-positive networks (Utevsky et al, 2014) and has been shown to be actively engaged in some attention-demanding tasks, possibly mediating the integration of inwardly-directed and externally-directed cognitive processes (Lyu et al, 2021). More recently, the precuneus has also been proposed as a key region for memory acquisition (Brodt et al, 2018; Brodt et al, 2016; Schott et al, 2019).…”
Section: Discussionmentioning
confidence: 99%